x-1/2+1=x-1 3-2(2y-1)=3(2y-1)-2 2/7(x-7)=2-2/3x 5x+1/6=9x+1/8-1-x/3 3/2|x+5|=5 解方程
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 08:33:57
x-1/2+1=x-13-2(2y-1)=3(2y-1)-22/7(x-7)=2-2/3x5x+1/6=9x+1/8-1-x/33/2|x+5|=5解方程x-1/2+1=x-13-2(2y-1)=3(
x-1/2+1=x-1 3-2(2y-1)=3(2y-1)-2 2/7(x-7)=2-2/3x 5x+1/6=9x+1/8-1-x/3 3/2|x+5|=5 解方程
x-1/2+1=x-1 3-2(2y-1)=3(2y-1)-2 2/7(x-7)=2-2/3x 5x+1/6=9x+1/8-1-x/3 3/2|x+5|=5 解方程
x-1/2+1=x-1 3-2(2y-1)=3(2y-1)-2 2/7(x-7)=2-2/3x 5x+1/6=9x+1/8-1-x/3 3/2|x+5|=5 解方程
x-1/2+1=x-1 x-1+2=2x-2 x=3
3-2(2y-1)=3(2y-1)-2 5=5(2y-1) 2y-1=1 y=1
2/7(x-7)=2-2/3x 2/7x-2=2-2/3x 1/7x+1/3x=2
10x=42 x=4.2
5x+1/6=9x+1/8-1-x/3 5x+1/6+x/3=9x+1/8-1
[7x+7]/6=[9x+9-8]/8 7[x+1]/6=9[x+1]/8-1
28[x+1]-27[x+1]=-24 [x+1]=-24 x=-25
3/2|x+5|=5 |x+5|=10/3 x=-5/3
若2/x-1/y=3,求[y/x-y/x-y(x-y/x-x+y)]/x-2y/x的值
(3x-y)^2+(3x+y)(3x-y),x=1,y=-2
二元一次方程 :2(x+y)-(x-y)=3 (x+y)-2(x-y)=1
(x-y)/(x+y)=3求( 3x-2y-1)/(x+y-5)
2(x+y)-3(x-y)=1 6(x+y)+(x-y)=51
{3(x+y)-4(x-y)=4 {x+y/2 + x-y/6=1
变量x,y满足约束条件,x+y>=3,x-y>=-1,2x-y
(x-y)^2+(x+y)(x-y) 其中 X =3 Y=-1
函数,y=3x/(x^2+x+1) ,x
函数y=3x/(x^2+x+1) (x
x+y+2(-x-y+1)=3(1-y-x)-4-(y+x-1),x+y=?
{(x+y)/2+(x-y)/3=1,(x+y)-5(x-y)=2.求x=?,y=?
化简 3x(x^2-x-1)-(x+1)(3x^-x) X^3(x-y)+x(y-x)
x²/xy-x/y 3x/4x+y - x-2y/4x+y (1-y/y+x)÷x/y²-x²
[3x^2-(x+y)(y-x)][2(-x-y)(y-x)+2x^2+3y^2],其中x=-2分之1,y=1.5
化简[(3x+4y)^2-(2x+y)(2x-y)+(-x+y)(5x-y)]除以-2y,其中x=-1,y=1
先化简 再求值 (2x-y)(y+x)-(x-2y)(2y+x)-(-3y+x)^2其(√x+1)+y^2+4=-4y
已知:2x+y=6,x-3y=1 求7y(x-3y)(x-3y)-2(3y-x)(3y-x)